'It was the worst possible timing': the response of UK Longitudinal Integrated Clerkships to Covid-19. Issue 5 (3rd September 2022) - EL. Brown, Megan; Parekh, Ravi; Anderson, Kevin; Mayat, Nabilah; McKeown, Andy
ABSTRACT: Covid-19 has altered medical education worldwide. Given recent events, UK Longitudinal Integrated Clerkships (LICs), which are relatively new innovations, may have changed in structure and delivery, or may have demonstrated resilience. Collating the responses and experiences of UK institutions may yield transferrable recommendations for institutions wishing to develop sustainable LICs. A mixed-methods survey concerning LIC prevalence, variety, and experiences of responses to Covid-19 was circulated to all 33 UK medical schools through academic networks. 25 survey responses were received, representing 20 institutions. 12 faculty completed follow up semi-structured interviews. 13 LICs were reported: 1 wasn't running during 2020, 5 were running unchanged, and 7 with alterations. 2 additional LICs were planned. Thematic analysis of free-text survey and interview responses revealed that relationships between faculty and institutions were central in facilitating recent adaptations to UK LICs. Given model flexibility, an increased drive to develop LICs was also evident. Barriers to adapting programmes included uncertainty regarding progression of Covid-19 restrictions and issues with secondary care access. Investing in faculty development and support networks could increase LIC sustainability. By highlighting the relative resilience of UK LIC placements during Covid-19, these findings offer important insight for the future delivery of sustainable LICs within, and beyond, the UK.